Pentru o abordare socială în domeniul sănătăţii. Factorii structurali ai determinării stării de sănătate - Precupețu, Iuliana; Pop, Cosmina-Elena (Calitatea Vieții, 2017)
This article argues in favor of a conceptual framework on social determinants of health that can allow analysis and intervention in the field of health. First, we look at the main theoretical perspectives on the social determinants of health. Second, we look at health status in European comparative perspective, and trends registered in time in health status in Romania. Finally, we detail an adapted framework on social determinants of health put forward by the World Health Organization and we focus on structural social determinants of health. In Romania, health status is problematic and marked by important inequalities, and while some positive trends have been noticed in time, our country still ranks among those with the least favorable situations in health status in the European Union. In case of Romania, the adoption of a framework on social determinants of health can guide the understanding of current health status based on existing data/research, can help in surveying all relevant factors that contribute to health, and can provide a starting point for research based policy.